1984
DOI: 10.1128/aem.48.2.380-385.1984
|View full text |Cite
|
Sign up to set email alerts
|

Substrate utilization by Legionella cells after cryopreservation in phosphate buffer

Abstract: The objective of this study was to evaluate by relatively simple metabolic tests the usefulness of buffers and energy sources commonly used in Legionella growth media. Legionella pneumophila serogroups 1 to 6, Legionella micdadei, and Legionella bozemanii were grown in an enriched charcoal-yeast extract diphasic medium. The cells were washed thrice, suspended in various buffers (pH 6.9) with 1 or 5 mM MgSO4, and used immediately or after controlled-rate cryopreservation. CO2 produced and C incorporated into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The advantages of studying the metabolic activities of campylobacters by the method described in this paper are flexibility and sensitivity. A large number of substrates can be used singly or in combination with unlabeled substrates (23). With due caution, this method can be applied to formate as the substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of studying the metabolic activities of campylobacters by the method described in this paper are flexibility and sensitivity. A large number of substrates can be used singly or in combination with unlabeled substrates (23). With due caution, this method can be applied to formate as the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The protein content of the cell preparations was determined by the Bio-Rad protein assay procedure (2), as described previously (23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early (radiotracer) experiments revealed that amino acids serve as the main carbon and energy source of L. pneumophila when growing in vitro in different media . From these experiments, Ser, Thr, Glu and Tyr were identified as preferred substrates in vitro , and Cys, Gln, Ser, Met, Val, Glu, Tyr, Thr and Arg were shown to support growth in vivo . In addition, the identification of high activity of Glu‐Asp transaminase in lysates of in vitro grown bacteria suggested that this activity is involved in the linkage of the TCA cycle to gluconeogenesis and anabolic pathways .…”
Section: Metabolic Features Of L Pneumophila In Vitromentioning
confidence: 99%
“…Various experimental studies and the analysis of various genome sequences revealed that L. pneumophila is auxotrophic for Arg, Cys, Ile, Leu, Met, Thr and Val, and the amino acids Arg, Cys, Ile, Leu, Met, (Phe), Ser, Thr, (Tyr) and Val are essential for growth . Cysteine is absolutely required for the growth of legionellae, and media must be supplemented with cysteine to support growth of L. pneumophila , but this is not true for L. oakridgensis , a less virulent Legionella species .…”
Section: Metabolic Features Of L Pneumophila In Vitromentioning
confidence: 99%